The effect of coumarin addition on the electrical characteristics of Al/Coumarin:CdO/p-Si/Al photodiode prepared by drop casting technique - Aslan, Fehmi; Esen, Hikmet; Yakuphanoğlu, Fahrettin (Elsevier Gmbh, 2019)
In this study, cadmium oxide thin films deposited on p-Si with different weight ratio of coumarin were prepared by drop casting technique. The effect of coumarin addition in different weight ratios was investigated on the electrical and photosensivity properties of Al/Coumarin:CdO/p-Si organic-inorganic hybrid photodiodes. The current-voltage (I-V) and capacity-conductivity-voltage (C-G-V) characteristics of the diodes were determined in the dark and under various illumination intensities. It is concluded that all samples have excellent rectification properties due to good rectifying ratios found from I-V characteristics of the devices. All photodiodes produced with different coumarin weight ratios were found to have higher photo-current under illuminated conditions than dark conditions. In addition, the highest I-photo/I-dark photosensitivity value was found as 448.78 for the device with a 5% coumarin doping rate under 5 V and 100 mW/cm(2) light intensity. Transient photo-current measurements showed that all devices are sensitive to light intensity. Furthermore, capacitance/conductivity-voltage measurements were performed at frequencies ranging from 10 kHz to 1 MHz. The fact that the capacity decreases and conductivity increases with the increasing frequency values was explained with the presence of interface states. The ideality factors of Al /Coumarin:CdO/p-Si/Al photodiodes, prepared with various coumarin doping ratios, are between 4.39 and 7.83. Additionally, the interfacial density (D-it) and serial resistance (R-s) values of the devices were determined to be dependent on the frequency and the coumarin concentration. As a result, produced Al/Coumarin:CdO/p-Si/Al organic-inorganic hybrid devices can be used as photocapacitors and/or photodiodes in electro-optic applications.
Keywords: Photodiode; Coumarin:CdO thin films; Electrical properties; Organic-inorganic semiconductor